CRISPR-Cas9 Mediated Capsule Gene Silencing in Escherichia coli - Bandehpour, Mojgan; Nafarieh, Tina; Zahedipour, Fatemeh; Tavasoli, Afsaneh; Kazemi, Bahram (Novelty in Biomedicine, 2018)
Background: Genomic engineering of Escherichia coli is applied to design and produce recombinant proteins as the new drugs. The aim of this study was to CRISPR-Cas9 mediated capsule gene silencing in E. coli. Materials and Methods: We suppressed genes involved in capsule expression of E.coli by CRISPR cas9 process. The constructed E.coli was confirmed by microscopic smear, transmission electron microscopy and T7 phage influence assay. Results: The results were shown that the inhibition of capsule production was carried out successfully and there was not any capsule layer around the bacteria. Conclusion: E. coli without any capsule around may proper for replacement of it with other molecules in future.